2019
DOI: 10.1242/jcs.226183
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania amazonensis hijacks host cell lysosomes involved in plasma membrane repair to induce invasion in fibroblasts

Abstract: Intracellular parasites of the genus Leishmania are the causative agents of leishmaniasis. The disease is transmitted by the bite of a sand fly vector, which inoculates the parasite into the skin of mammalian hosts, including humans. During chronic infection the parasite lives and replicates inside phagocytic cells, notably the macrophages. An interesting, but overlooked finding, is that other cell types and even non-phagocytic cells have been found to be infected by Leishmania spp. Nevertheless, the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 42 publications
0
39
0
Order By: Relevance
“…Interestingly, extracellularly added ASM also promotes T. cruzi entry in ASM‐depleted cells, indicating that these parasites subvert the ASM‐mediated plasma membrane repair process as a strategy for host cell invasion (Fernandes et al, ). This invasion strategy appears to be more widespread than originally thought, having been demonstrated for fibroblast invasion by the T. cruzi ‐related protozoan Leishmania (Cavalcante‐Costa et al, ) and for adenovirus infections (Luisoni et al, ). Earlier studies found a role for ASM in host cell entry by the bacteria Neisseria and Pseudomonas and Sindbis viruses, although in these cases the origin of the extracellular ASM generating ceramide‐enriched plasma membrane domains and pathogen internalisation was unknown (Grassme et al, ; Jan, Chatterjee, & Griffin, ; Simonis, Hebling, Gulbins, Schneider‐Schaulies, & Schubert‐Unkmeir, ).…”
Section: Asm Released From Lysosomes Remodels the Cell Surface Promotmentioning
confidence: 91%
“…Interestingly, extracellularly added ASM also promotes T. cruzi entry in ASM‐depleted cells, indicating that these parasites subvert the ASM‐mediated plasma membrane repair process as a strategy for host cell invasion (Fernandes et al, ). This invasion strategy appears to be more widespread than originally thought, having been demonstrated for fibroblast invasion by the T. cruzi ‐related protozoan Leishmania (Cavalcante‐Costa et al, ) and for adenovirus infections (Luisoni et al, ). Earlier studies found a role for ASM in host cell entry by the bacteria Neisseria and Pseudomonas and Sindbis viruses, although in these cases the origin of the extracellular ASM generating ceramide‐enriched plasma membrane domains and pathogen internalisation was unknown (Grassme et al, ; Jan, Chatterjee, & Griffin, ; Simonis, Hebling, Gulbins, Schneider‐Schaulies, & Schubert‐Unkmeir, ).…”
Section: Asm Released From Lysosomes Remodels the Cell Surface Promotmentioning
confidence: 91%
“…(Aikawa et al, 1978) and Toxoplasma gondii (Mordue et al, 1999). Invasion can also occur through the subversion of physiological host cell processes, such as lysosome-triggered Ca 2+ -dependent endocytosis, which is used by all nucleated cells to repair wounded PMs (Corrotte and Castro-Gomes, 2019); this pathway has previously shown to occur for Trypanosoma cruzi (Rodríguez et al, 1996;Fernandes et al, 2011), and also more recently by our lab for Leishmania amazonensis (Cavalcante-Costa et al, 2019). Large parasites can be equally phagocytosed, if they are able to resist phagocytic degradation and live within phagocytic cells, such as protozoans of the genus Leishmania (Zenian et al, 1979).…”
Section: Introductionmentioning
confidence: 69%
“…In fact, it has long been described that promastigotes can also invade nonphagocytic cells (Bogdan et al, 2000;Minero et al, 2004;Holbrook and Palczuk, 1975;Schwartzman and Pearson, 1985). Recent work from our group has unveiled a new non-phagocytic route of promastigote invasion without any involvement of the host cell cytoskeleton, thereby providing definitive evidence for an entry mechanism other than phagocytosis (Cavalcante-Costa et al, 2019). This pathway involves the Ca 2+ -dependent recruitment and exocytosis of host cell lysosomes to the parasite invasion site, where they instantly fuse with the PM, much like in the invasion mechanism described above for T. cruzi.…”
Section: Cell Invasion By Trypanosoma Cruzimentioning
confidence: 91%
See 2 more Smart Citations